DINAMIKA PERBEDAAN PENDAPAT TERKAIT KEWARISAN ANAK KETIKA FORMULASI KOMPILASI HUKUM ISLAM - Muhammad Fadhlan Is (STIS Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2020)
An opinion differencein the stipulation of Islamic Law is not a new thing. It already existed even when the Prophet was still alive. Likewise, during the KHI formulation, it was clear that there was a dynamic of opinion differenceamong Islamic Law, Customary Law and Civil Law (Burgerlijk Wetboek) which were intersected in influencing the stipulation of the Islamic Lawin the country. There are many factorsthat lead to the dynamics of different opinions; among others is the existence of Civil Law products (Burgerlijk Wetboek) which had been applied before KHI.This colonial Law is what influences the national lawyers’ pattern of thinkingin determining Islamic law in KHI. The results of the study show the fact that the formulation of KHI through a structural approach is top down from the central government, but still involves the role of the ulama, scholars and practitioners of Islamic law. KHI material absorbs fiqh that is familiar in the country. The dynamics of differences of opinion are found in three patterns of Islamic Law thought that emerged at that time. First, the literalisasi group, which is a group that opposes thoughts that violate the nash qat'i. Secondly, the group is assimilative, this group tries to find a new interpretation in understanding nash qat'i. The three groups are Harmonized, Characteristics of this group may be out of zahir nash, if judging there are provisions that can be an alternative, inheritance is included in the category of mu'amalat worship which must be open to accepting changes by considering the interests and eliminating the narrowness in society.